PENGARUH NILAI ASET TIDAK BERWUJUD DAN PENELITIAN DAN PENGEMBANGAN TERHADAP NILAI PASAR PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2010 ) - Letsa Soraya; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This study aims to examine whether intangible assets value in 2009 and 2010 is difference. This study also aims to examine the influence of intangible assets value (INTAV) and research&development on corporate market value. This study used purposive sampling method with criteria as follows : (1) Manufacturing companies listed and actively traded on Indonesia Stock Exchange (IDX) during 2009-2010, (2) Manufacturing companies that published financial statement at 31 December 2009 and 31 December 2010 completely, (3) Manufacturing companies whose a record of stock price at the time of closing, and (4) Manufacturing companies whose INTAV positive. Based on these criteria, obtained 255 companies over two year period of observation. Then, there are 8 companies which didn’t publish financial statement completely, 114 whose INTAV negative, and 13 samples that included outlier should be excluded from samples of observation. So, the final sample is 120 firms. Two analysis used to test the hypotheses are multiple regression analysis and t-test. The result showed that (1) intangible assets value and research&development have a positive and significant influence on corporate market value (CMV), (2) intangible assets value in 2009 and 2010 is difference.